(untitled) (Superficies y Vacío, 2017)
GaAs buffer layer in InAs/GaAs quantum dots (QDs) was investigated by Photoreflectance (PR) technique at 300 K. PR spectra obtained were compared with commercial GaAs sample PR spectra, and they were analyzed by using the derivative Lorentzian functions as proposed by Aspnes in the middle field regimen. PR spectra in InAs/GaAs QDs sample was attributed to the photoreflectance response in the GaAs buffer layer. Band bending energies were calculated for laser intensities from 1 mW to 21 mW. The photoreflectance comparative study in the samples was realized considering the difference in the parameters: electric field on the surface, broadening parameter, energy gained by photoexcited carriers due to the electric field applied, frequency of light and heavy holes and band bending energy values. The results suggest that the presence of InAs quantum dots increases the light and heavy holes frequencies and the band bending energy values; and decreases the electric field on the surface, the broadening parameter and the energy gained by photoexcited carriers. We found that InAs QDs presence modifies the surface electrical field around one order of magnitude in the GaAs buffer layer and this behavior can be attributed to surface passivation.